Development And Characterization Of Polymer Gel Dosimeter Doped With Gold Nanoparticles - Hisham, Muhd Hazwan Hakim (2023)
This study makes use of the advantage of normoxic polymer gels which are composed of two different monomer, 2-Hydroxyethyl Acrylate (HEA) and 2-Hydroxyethyl Methacrylate (HEMA) and N,N’-Methylene-bisacrylamide (BIS) as the crosslinker. To enable the fabrication of polymer gel to be done under the normal atmospheric condition, Ascorbic Acid is added as the anti-oxidant. As past studies had mainly been done using high energy sources, this study also focuses on using high energy x-ray source as in linear accelerator (LINAC) as well as a diagnostic x-ray unit as the main energy source. Dose sensitivity is property investigated in studying the behavior of dose distribution in the polymer gel. Magnetic Resonance Imaging (MRI) is the main polymerization imaging readout instrument before the images are used for further calculation of dose sensitivity. The results obtained are backed up by the analysis using UV-Visible spectrophotometer. In general, the dose sensitivity is directly proportional to the irradiation energy, monomer concentration and AuNPs size. When HEMA is used as the monomer, higher irradiation dose by LINAC increases the absorption of light. This is true for all the size of AuNPs used in this study (15nm, 20 nm, 40nm, 50nm and 80nm). Except for 50nm AuNP size, samples irradiated with dose of 30Gy shows a decreasing absorption of light at wavelength over 500nm. The decreasing pattern goes below than the samples irradiated with 10Gy and 20Gy. The result shows that at low x-ray energy, the size of AuNP has an impact on the polymerization. Higher concentration of monomer does not affect the polymerization significantly at the low energy level. At high x-ray energy